Spontaneous splenic rupture following mitral valve replacement for infective endocarditis successfully managed with splenic artery embolisation. Issue 12 (16th September 2020) - Shafi, Ahmed Mohamed Abdel; Lee, Michelle; Balmforth, Damian; Lall, Kulvinder
Abstract: We report a rare case of infective endocarditis complicated by postoperative splenic rupture. A patient underwent urgent mitral valve replacement for infective endocarditis believed to be associated with a recent spinal surgical intervention. The patient developed haemodynamic compromise on the third day postoperatively. Computed tomography showed a splenic rupture as the cause. The patient underwent emergency radiological intervention with coil embolization avoiding the need for a splenectomy and was discharged home.